Robotic assistance system for cone-beam computed tomography-guided percutaneous needle placement - Kostrzewa, Michael; Rothfuß, Andreas; Pätz, Torben; Kühne, Markus; Schönberg, Stefan; Diehl, Steffen J.; Stallkamp, Jan; Rathmann, Nils-Andreas (CardioVascular and interventional radiology, 2022)
Purpose The study aimed to evaluate a new robotic assistance system (RAS) for needle placement in combination with a multi-axis C-arm angiography system for cone-beam computed tomography (CBCT) in a phantom setting.